Counseling and Reservation Information System Integrated Public Service Complaints at DP3APPKB Salatiga - Maghtani, Bagas Erdo Al; Kristianto, Budhi (Universitas Negeri Semarang, 2025)
The purpose of this final task is to design and develop a website-based complaint and re-inspection information system, to implement a system that makes it easier for the public to submit complaints and conduct re-inspection online and to provide complaint data management features and a structured re-inspection schedule for DP3APPKB administrators. System Metode system development that will be created using CSS model and Visual Studio Code. Cascading Style Sheet (CSS) in its standard language. As defined in Quote and Wikipedia, CSS is a